2016
DOI: 10.1039/c6dt03398a
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-band red emitting phosphor BaTiF6:Mn4+: preparation, characterization and application for warm white LED devices

Abstract: As a new class of non-rare-earth red phosphors for high-efficiency warm white light-emitting diodes (white LEDs), Mn ion activated fluoride compounds have been extensively investigated recently and hold the potential to supersede commercial rare earth doped nitride phosphors. Herein, a series of Mn ions doped BaTiF phosphors have been prepared via the hydrothermal route using citric acid as a surfactant. After a systematic investigation, we illustrate the effects of reaction time, nominal concentration of HF s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In recent years, Mn 4 + doped fluoride phosphors have attracted widespread attention in the fields of liquid crystal display (LCD) [1] and solid-state lighting (SSL). [2] So far, a series of Mn 4 + -doped fluoride red-emitting phosphors, such as A 2 XF 6 : Mn 4 + (A = NH 4 , Li, Na, K, Rb and Cs; X = Si, Ti, Ge, Sn, Zr and Hf), [3][4][5][6] BXF 6 (6H 2 O) : Mn 4 + (B = Ba and Zn), [7][8][9][10] A 3 MF 6 : Mn 4 + (M = Al, Ga and Sc), [1,[11][12][13] A 2 NF 7 : Mn 4 + (N = Ta and Nb), [14,15] A 2 NO x F 6-x : Mn 4 + (x = 1, N = Ta and Nb; x = 2, N = W and Mo) [16][17][18][19] and A 3 XF 7 : Mn 4 + [20] has been reported. Unfortunately, although fluoride phosphors with a narrow emission at around 630 nm exhibit unique luminescence performance under blue light excitation, the deterioration of luminescent properties as a result of obvious hydrolysis has limited their large-scale application.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Mn 4 + doped fluoride phosphors have attracted widespread attention in the fields of liquid crystal display (LCD) [1] and solid-state lighting (SSL). [2] So far, a series of Mn 4 + -doped fluoride red-emitting phosphors, such as A 2 XF 6 : Mn 4 + (A = NH 4 , Li, Na, K, Rb and Cs; X = Si, Ti, Ge, Sn, Zr and Hf), [3][4][5][6] BXF 6 (6H 2 O) : Mn 4 + (B = Ba and Zn), [7][8][9][10] A 3 MF 6 : Mn 4 + (M = Al, Ga and Sc), [1,[11][12][13] A 2 NF 7 : Mn 4 + (N = Ta and Nb), [14,15] A 2 NO x F 6-x : Mn 4 + (x = 1, N = Ta and Nb; x = 2, N = W and Mo) [16][17][18][19] and A 3 XF 7 : Mn 4 + [20] has been reported. Unfortunately, although fluoride phosphors with a narrow emission at around 630 nm exhibit unique luminescence performance under blue light excitation, the deterioration of luminescent properties as a result of obvious hydrolysis has limited their large-scale application.…”
Section: Introductionmentioning
confidence: 99%
“…34 Previous work has revealed that Mn 4+ emits red light in the octahedral coordination geometry. 17 ions in Sr 3 (W,Mn)O 6 . The optimal Mn 4+ dopant content was found to be x = 0.005.…”
Section: Resultsmentioning
confidence: 62%
“…Mn 2+ can show different PL bands in the range of 450–610 nm, , while Mn 3+ , Mn 5+ , and Mn 6+ ions show near-infrared emissions, and the Mn 7+ emission has not been detected so far . Previous work has revealed that Mn 4+ emits red light in the octahedral coordination geometry . We thus assign the red light emission to the 2 E g → 4 A 2g transition of octahedrally coordinated Mn 4+ ions in Sr 3 (W,Mn)­O 6 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been great interest in studying and developing rare earth (RE) luminescence materials on account of their potential applications, such as liquid lasers, photoelectric devices, nanolabels, multimodality bioimaging contrast agents, television tubes, mobile telephone screens, fluorescent lamps, and the promising white light-emitting diodes. Among all kinds of RE luminescence materials, RE fluoride (such as GdF 3 ) luminescence materials have many excellent properties, for instance, long lifetime, lower energy consumption, high luminous efficiency, and environmentally friendliness, and so on. Therefore, GdF 3 is considered to be a prominent luminescent host material.…”
Section: Introductionmentioning
confidence: 99%